POTENSI DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KOTA PONTIANAK - B2052151006, HAMYANI (Jurnal Ekonomi Daerah (JEDA), 2017)
The study entitled "The Potential Hotel’s Taxes and Contributions To The Local Revenue (PAD) in Pontianak Municipality. This aiming to know and analyze potent review, contributions and effectiveness and tahn  to predictions of hotel tax revenue as a principal component own revenue (PAD) of Pontianak. The variables studied is a hotel occupancy rate and turnover reception’shotel as a base bases hotel tax. Used a primary and secondary data that got of respondents/employee of hotel as 16 person from classified (star’s) hotels and 21 non classified (non star’s) hotel. The analysis tool used is simple regression analysis and calculation of the turnover of the company/hotel. The result show that the contributions of hotel’s tax of PAD (in percentage) occurred decline the average as -0.74%, athough the amount was to rised during year 2011 to 2015. Based on the findings of the Tax Collection Hotel estimate reached Rp28.077.922.581,82, it is larger meanwhile hotel tax of 2016 actual as Rp25.700.000.000,00 or 91.53%. This is to effective by acceptance criteria effectiveness so effective already, however it findings that revenue collection can still be improved. The projection culations of hotel taxs show that nominal value is increased but it growth is likely to decline from year to year. This trend the same the previous year.  The  reression operates shown tha  tax effect of  PAD formed relationship  to Y (PAD) = -16.83733 + 17,9966(hotel tax), and very significant high and the R2 (96,113%), which means that the tax yery dominant to PAD. It’s influence is positive regression coefficient as  17,99.  It means  if hotel tax increases/decreases one unit then also PAD increases/decreases 17.99 to the same, with the asuming other variables variables. Keywords : Hotel Tax, Hotel Occupancy Rate, Classified Hotel, non Classified  hotels.